Pengaruh Strategi Content Marketing dan Mekanisme Pembayaran COD terhadap Keputusan Pembelian pada Social Commerce Tiktok Shop - Reni Suci Wahyuni; Kuswadi Rustam; Retno Setioningsih (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2026)
The development of social commerce has encouraged the integration of content-based marketing strategies with transaction mechanisms that enhance consumers’ perceived security. TikTok Shop, as a video-based e-commerce platform, introduces new dynamics in consumers’ purchase decision-making processes. This study aims to analyze the effects of content marketing and the Cash on Delivery (COD) system on consumers’ purchase decisions on the TikTok Shop e-commerce platform. This research adopts a quantitative approach using a survey method involving 101 TikTok Shop users in Indonesia who have made purchases on the platform. Data were collected through an online questionnaire and analyzed using multiple linear regression with the assistance of SPSS. The results indicate that content marketing and the Cash on Delivery (COD) system have positive and significant effects on purchase decisions, both partially and simultaneously. Partially, the COD system exerts a more dominant influence than content marketing. The coefficient of determination shows that the independent variables explain a substantial proportion of the variance in consumers’ purchase decisions. These findings suggest that purchase decisions on TikTok Shop are influenced by a combination of content quality and payment mechanisms that reduce consumers’ perceived risk.